mTOR regulates cocaine-induced behavioural sensitization through the SynDIG1–GluA2 interaction in the nucleus accumbens - Li Hong-chun; Zhang Jia-mei; Xu Rui; Wang Yong-hai; Xu Wei; Chen Rong; Wan Xue-mei; Zhang Hao-luo; Wang Liang; Wang Xiao-jie; Jiang Lin-hong; Liu Bin; et al. (Acta Pharmacologica Sinica; Vol 43, No 2 (February 2022): Acta Pharmacologica Sinica, 2022)
Behavioral sensitization is a progressive increase in locomotor or stereotypic behaviours in response to drugs. It is believed to contribute to the reinforcing properties of drugs and to play an important role in relapse after cessation of drug abuse. However, the mechanism underlying this behaviour remains poorly understood. In this study, we showed that mTOR signaling was activated during the expression of behavioral sensitization to cocaine and that intraperitoneal or intra-nucleus accumbens (NAc) treatment with rapamycin, a specific mTOR inhibitor, attenuated cocaine-induced behavioural sensitization. Cocaine significantly modified brain lipid profiles in the NAc of cocaine-sensitized mice and markedly elevated the levels of phosphatidylinositol-4- monophosphates (PIPs), including PIP, PIP2, and PIP3. The behavioural effect of cocaine was attenuated by intra-NAc administration of LY294002, an AKT-specific inhibitor, suggesting that PIPs may contribute to mTOR activation in response to cocaine. An RNA- sequencing analysis of the downstream effectors of mTOR signalling revealed that cocaine significantly decreased the expression of SynDIG1, a known substrate of mTOR signalling, and decreased the surface expression of GluA2. In contrast, AAV-mediated SynDIG1 overexpression in NAc attenuated intracellular GluA2 internalization by promoting the SynDIG1–GluA2 interaction, thus maintaining GluA2 surface expression and repressing cocaine-induced behaviours. In conclusion, NAc SynDIG1 may play a negative regulatory role in cocaine-induced behavioural sensitization by regulating synaptic surface expression of GluA2.